The Effect of Flipped Classroom Based on Disaster Map Visualization in Disaster Mitigation Learning on Students’ Self-Efficacy and Critical Thinking Skills - Astawa, I. B. M.; Citrawathi, D. M.; Sudiana, I. K.; Wulandari, I. G. A. A. M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Disaster mitigation material in geography learning requires not only critical thinking skills but also independence and optimism from students. In this regard, the effective approach needed relies not only on theory but also on practice in independent assignments and exercises. It makes limited face-to-face learning, which has been applied recently, unable to optimize learning outcomes. This study aims to analyze the impact of flipped classroom learning based on disaster map visualization on students' self-efficacy and critical thinking skills in disaster mitigation materials. The study used a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of the experimental class (30 students) and the control class (30 students), which were determined randomly after the equivalence test. Data on critical thinking skills were collected using a test method in 10 description items, and self-efficacy data were collected using a questionnaire consisting of 30 statements. The data were analyzed using quantitative descriptive and inferential statistical analysis with MANOVA. The results show a significant effect simultaneously or partially with the sig value. 0.05, so it can be concluded that there is an effect of flipped classroom learning based on disaster map visualization on students' self-efficacy and critical thinking skills in disaster mitigation materials.